Fiscal spending multiplier calculations based on input-output tables – an application to EU member states - Toralf Pusch (Intervention. European Journal of Economics and Economic Policies, 2012)
Fiscal spending multiplier calculations have attracted considerable attention in the aftermath of the global financial crisis. Much of the current literature is based on VAR estimation methods and DSGE models. In line with the Keynesian literature we argue that many of these models probably underestimate the fiscal spending multiplier in recessions. The income-expenditure model of the fiscal spending multiplier can be seen as a good approximation under these circumstances. In its conventional form this model suffers from an underestimation of the multiplier due to an overestimation of the import intake of domestic absorption. In this article we apply input-output calculus to solve this problem. Multipliers thus derived are comparably high, ranging between 1.4 and 1.8 for many member states of the European Union. GDP drops due to budget consolidation might therefore be substantial in times of crisis.
Keywords: B22; C67; E12; E62; 330; fiscal spending multiplier; input-output calculus; income-expenditure model; European Union; EU